The emerging concern of IMP variants being resistant to the only IMP-type metallo-β-lactamase inhibitor, xeruborbactam - Le Terrier, Christophe (2025)
Metallo-β-lactamases (MBLs) of IMP type are not inhibited by currently commercialized β-lactamase inhibitors, including taniborbactam (TAN), which inhibits only NDM- and VIM-type enzymes. However, the development of xeruborbactam (XER), which additionally inhibits IMP enzymes, may provide effective drug combinations such as meropenem-XER (MEM-XER) against most MBL producers. Thirty-two IMP-producing clinical gram-negative isolates were tested for MEM-XER. Susceptibility testing of β-lactams with TAN or XER at 4 or 8 µg/mL was performed. Noticeably, MEM-XER remained ineffective against all IMP-producing Pseudomonas aeruginosa isolates. By contrast, supplementation with XER significantly lowered MEM MICs for several IMPproducing Enterobacterales isolates, except for isolates and recombinant E. coli strains producing IMP-6, IMP-10, IMP-14, and IMP-26. Interestingly, IMP-59 producers showed susceptibility to both TAN- and XER-based combinations, although IMP enzymes are not supposed to be inhibited by TAN. Determinations of 50% inhibitory concentration (IC50) values of XER showed values being >15-fold higher for IMP-6, IMP-10, IMP-14, and IMP-26 compared with IMP-1. Interestingly, the IC50 value of TAN for IMP-59 was found in the same range as that for NDM-1 (7 µM). Finally, structural analyses and molecular modeling simulations indicated that the Ser262Gly mutation in IMP-6 may alter the electronic properties of the active site, whereas the Phe residue in IMP-10 may exert a steric effect counteracting XER binding. Resistance to XER in IMP-6, IMP-10, IMP-14, and IMP-26 variants, conferring resistance to MEM-XER, might be considered a serious concern since MEM-XER will be supposed to be a salvage therapy for MBL-, and especially IMP-producing Enterobacterales infections.